2017
DOI: 10.1111/eip.12461
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between the frequency and severity of non‐suicidal self‐injury and suicide attempts in youth with borderline personality disorder

Abstract: The prevalence of NSSI and suicide attempts among youth presenting for their first treatment of BPD appear to be perilously high, considerably higher than rates reported by adults with BPD. Findings suggest that clinicians should give more weight to average levels of impulsivity and depression, rather than the absolute frequency and severity of NSSI, when assessing for risk of suicide attempts. Notwithstanding this, a relative increase in the frequency and severity of NSSI appears to be predictive of a forthco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
38
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(42 citation statements)
references
References 47 publications
3
38
0
1
Order By: Relevance
“…Our results indicate that a higher number of NSSI methods (OR = 1.81) significantly predicts lifetime suicide attempts, which is in line with previous research (e.g., (7,19). Consistent with findings from Andrewes et al (51) and Burke et al (27), higher levels of depressive symptoms significantly predict current suicidal ideation (OR = 1.09). Previous studies (27,28) found that the anti-suicide function was an important predictor of occurrence of suicidal ideation.…”
Section: Discussionsupporting
confidence: 92%
“…Our results indicate that a higher number of NSSI methods (OR = 1.81) significantly predicts lifetime suicide attempts, which is in line with previous research (e.g., (7,19). Consistent with findings from Andrewes et al (51) and Burke et al (27), higher levels of depressive symptoms significantly predict current suicidal ideation (OR = 1.09). Previous studies (27,28) found that the anti-suicide function was an important predictor of occurrence of suicidal ideation.…”
Section: Discussionsupporting
confidence: 92%
“…In part, this might reflect the natural history of self‐harm in young people or secular trends that reflect the different eras in which these cohorts were collected. However, it does accord with recent data in 107 outpatient youth (15–25 years old) with BPD reporting a 76% 12‐month prevalence for self‐mutilation and a 66% 12‐month prevalence for suicide attempts . This does give one pause for thought regarding where such young patients with extreme levels of self‐mutilation might end up later in life?…”
supporting
confidence: 75%
“…NSSI is a public health problem that cannot be ignored by college students, which seriously damages their physical and mental health. Studies have shown that early NSSI can lead to suicidal behavior and other mental illnesses later in life [33,34,35].…”
Section: Discussionmentioning
confidence: 99%